Privatizing Social Security Under Balanced-Budget Constraints: A Political-Economy Approach - Assaf Razin; Efraim Sadka (Center for Economic Studies and ifo Institute (CESifo), 2003)
The aging of the population shakes the public finance of pay-as-you-go social security systems. We develop a political-economy framework in which this demographic change leads to the downsizing of the social security system, and, as a consequence, to the emergence of supplemental individual retirement programs. Making the balanced-budget rule (of the type of the Stability and Growth Pact in the EU) more flexible, to accommodate a one-shot cost of the social security reforms, is shown to facilitate the political-economy transition from a national to a private pension system, through an endogenously determined shift in the political-economy equilibrium
Keywords: 330